2022
DOI: 10.3390/agriculture12111967
|View full text |Cite
|
Sign up to set email alerts
|

Insect Detection in Sticky Trap Images of Tomato Crops Using Machine Learning

Abstract: As climate change, biodiversity loss, and biological invaders are all on the rise, the significance of conservation and pest management initiatives cannot be stressed. Insect traps are frequently used in projects to discover and monitor insect populations, assign management and conservation strategies, and assess the effectiveness of treatment. This paper assesses the application of YOLOv5 for detecting insects in yellow sticky traps using images collected from insect traps in Portuguese tomato plantations, ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 80 publications
0
0
0
Order By: Relevance
“…Our study yields similar results in this regard. Domingues et al (2022) detected certain pests (such as bemisia tabaci, helicoverpa armigera) using sticky traps with YOLOv5, reaching a 94.4% mAP_0.5, with a precision and recall of 88% and 91%, respectively, using YOLOv5x. In their experiment, Zhang et al (2023) observed six diverse pests, including tobacco whiteflies, leaf miners, aphids, fruit flies, thrips, and houseflies.…”
Section: Analysis Of Training Yolov5s V5m V5l Resultsmentioning
confidence: 99%
“…Our study yields similar results in this regard. Domingues et al (2022) detected certain pests (such as bemisia tabaci, helicoverpa armigera) using sticky traps with YOLOv5, reaching a 94.4% mAP_0.5, with a precision and recall of 88% and 91%, respectively, using YOLOv5x. In their experiment, Zhang et al (2023) observed six diverse pests, including tobacco whiteflies, leaf miners, aphids, fruit flies, thrips, and houseflies.…”
Section: Analysis Of Training Yolov5s V5m V5l Resultsmentioning
confidence: 99%
“…Automatic image identification technologies based on computer vision are promising in insect detection, as documented in the literature (Ahmad et al, 2022;Júnior and Rieder, 2020;Zacarés et al, 2018). They have been implemented in numerous applications in managing insect disease vectors and controlling pests, such as agricultural and forest pests (Domingues et al, 2022;Duarte et al, 2022;Mendoza et al, 2023), in the classification of parasitised fruit fly pupae (Marinho et al, 2023), the detection of pine pests (Ye et al, 2022), the segmentation of ecological images featuring (Filali et al, 2022), the identification of whitefly (Kamei, 2023), and the automated counting of mosquito eggs (Javed et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…A specific example of a sensing device is the automated insect trap which is used in pest management. Automated traps are essential for keeping track of insect activity and are frequently used in pest population forecasting [2]. Images taken by the traps carry a huge amount of data and sophisticated data analysis methods are needed to extract the necessary information which can be used for decision making.…”
mentioning
confidence: 99%